Delay of computed tomography is associated with poor outcome in patients with blunt traumatic aortic injury: A nationwide observational study in Japan. Issue 35 (August 2018) - Katayama, Yusuke; Kitamura, Tetsuhisa; Hirose, Tomoya; Kiguchi, Takeyuki; Matsuyama, Tasuku; Sado, Junya; Kiyohara, Kosuke; Izawa, Junichi; Tachino, Jotaro; Ebihara, Takeshi; Yoshiya, Kazuhisa; Nakagawa, Yuko; et al.
Abstract : Abstract: According to guidelines from the Eastern Association for the Surgery of Trauma, computed tomography (CT) with intravenous contrast is strongly recommended to diagnose clinically significant blunt traumatic aortic injury (BTAI). However, it remains unclear whether the timing of CT scanning is associated with the prognosis of BTAI patients. We extracted data on emergency patients who suffered a BTAI in the chest and/or the abdomen from 2004 to 2015 from the Japanese Trauma Data Bank, a nationwide trauma registry. The primary outcome was death in the emergency department (ED) and secondary outcome was discharge to death. In addition, we assessed the relationship between death in the ED and the timing of CT scanning by shock status in subgroup analysis. We divided these patients into the tertile groups of early (⩽26 minutes), middle (27–40 minutes), and late (≥41 minutes) phases based on the time interval from hospital arrival to start of first CT scanning, and assessed death of BTAI patients in the ED by CT scanning time with the use of a multivariable logistic regression model. In total, 421 patients who suffered BTAI in the chest and/or the abdomen were eligible for our analysis. The proportion of patients dying at hospital admission was 7.7% (11/142) in the early group, 11.1% (15/135) in the middle group, and 17.6% (25/144) in the late group. In a multivariable logistic regression adjusted for confounding factors, the adjusted odds ratio (AOR) of death in the ED was 1.833 (95% confidence interval [CI]: 0.601–5.590, P  = .287) in the middle group and 2.832 (95% CI: 1.007–7.960, P  = .048) in the late group compared with the early group. Compared with the early group, the late group tended to have a higher rate of discharge to death (AOR: 1.438, 95% CI: 0.735–2.813). In the patients with shock, the AOR was 3.292 (95% CI: 0.495–21.902) in the middle group and 6.039 (95% CI: 0.990–36.837) in the late group compared with the early group. This study revealed that a longer time interval from hospital arrival to CT scanning was associated with higher mortality in the ED in patients with BTAI.